URGENSI PENGELOLAAN KELAS; SUATU ANALISIS FILOSOFIS DAN PEMAHAMAN DASAR BAGI KALANGAN PENDIDIK DI PESANTREN - Djuwairiyah Djuwairiyah; Moh. Nawafil (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Abstract: technological development and globalization flow have got change rapidly from one sector to another sector. That matter becomes a vital indicator to Pesantren for upgrade and keeping the qualities of graduates. So that many efforts do to provide militant, integrity, clever, and creative cadres who can give a huge contribution to the development of Indonesia country. Lesson activity that made more active and communicative can stimulate student to have enthusiasm, motivation, and concentration to get the goal of learning. One of the important competencies that have to owned by teacher based on the two ways communication paradigm is class management. Class management is a systematic and structured effort to get the goal of learning activities. The urgency of class management for the teacher in pesantren caused it can provide student to get actual work in thinking, interaction, and argue abilities. Keywords: Class Management, Teacher, Pesantren.